Multiple Mechanical Gradients are Responsible for the Strong Adhesion of Spider Attachment Hair. Issue 37 (2nd August 2020) - Flenner, Silja; Schaber, Clemens F.; Krasnov, Igor; Stieglitz, Hergen; Rosenthal, Martin; Burghammer, Manfred; Gorb, Stanislav N.; Müller, Martin
Abstract: Wandering spiders climb vertically and walk upside‐down on rough and smooth surfaces using a nanostructured attachment system on their feet. The spiders are assumed to adhere by intermolecular van der Waals forces between the adhesive structures and the substrate. The adhesive elements are arranged highly ordered on the hierarchically structured attachment hair (setae). While walking, it has been suggested that the spiders apply a shear force on their legs to increase friction. However, the detailed mechanical behavior of the hair's structures during attachment and detachment remains unknown. Here, gradients of the mechanical properties of the attachment hair on different length scales that have evolved to support attachment, stabilize adhesion in contact, and withstand high stress at detachment, examined by in situ experiments, are shown. Shearing helps to self‐align the adhesive elements with the substrate. The study is anticipated to contribute to the development of optimized artificial dry adhesives. Abstract : Nanostructured adhesive hair on the feet of spiders is responsible for strong adhesion, enabling the animals to walk upside down. Using scanning nanofocus X‐ray scattering under force control, the mechanism of alignment and consequently intimate contact, leading to adhesion of the nanostructures to a surface, is examined. The results show excellent adaptation of the biological structures for their specific function.